Tracking of an Oral Salmonella-Based Vaccine for Type 1 Diabetes in Non-obese Diabetic Mice - Mbongue, Jacques C.; Alhoshani, Ali; Rawson, Jeffrey; Garcia, Pablo A.; Gonzalez, Nelson; Ferreri, Kevin; Kandeel, Fouad; Husseiny, Mohamed I. (Frontiers in Immunology, 2020)
Type 1 diabetes (T1D) arises secondary to immune-driven destruction of pancreatic β-cells and manifests as insulin-deficient hyperglycemia. We showed that oral vaccination with live attenuated Salmonella, which simultaneously delivers autoantigens and a TGFβ expression vector to immune cells in the gut mucosa, provides protection against the progression of T1D in non-obese diabetic (NOD) mice. In this study we employed the Sleeping Beauty (SB) transposon system that is composed of a transposase and transposon encoding the td-Tomato to express red fluorescent protein (RFP) to permanently mark the cells that take up the Salmonella vaccine. After animal vaccination, the transposon labeled-dendritic cells (DCs) with red fluorescence appeared throughout the secondary lymphoid tissues. Furthermore, Sleeping Beauty containing tgfβ1 gene (SB-tgfβ1) co-expressed TGFβ and RFP. The labeled DCs were detected predominantly in Peyer’s patches (PP) and mesenteric lymph nodes (MLN) and expressed CD103 surface marker. CD103+ DCs induced tolerogenic effects and gut homing. TGFβ significantly increased programmed death-ligand-1 (PDL-1 or CD274) expression in the DCs in the MLN and PP of treated mice. Also, TGFβ increased cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) levels in CD4+ cells in MLN and PP. Interestingly, DCs increased in all lymphatic organs of mice vaccinated with oral live Salmonella-based vaccine expressing preproinsulin (PPI), in combination with TGFβ, IL10 and subtherapeutic-doses of anti-CD3 mAb compared with vehicle-treated mice. These DCs are mostly tolerogenic in MLN and PP. Furthermore the DCs obtained from vaccine-treated but not vehicle-treated mice suppressed in vitro T cell proliferation. These data suggest that the MLN and the PP are a central hub for the beneficial anti-diabetic effects of an oral Salmonella-based vaccine prevention of diabetes in rodents.